Singing in Zion : Music and Song in the Life of One Arkansas Family - Cochran, Robert, 1943- (Book collections on Project MUSE., 1999)
Cochran has included an appendix of over eighty songs that range from well-known folk material like "Sweet Lorraine" and "Barbara Allen" to lesser-known songs such as "The Frozen Girl" and "Seven Years with the Wrong Man." The sisters' comments reveal the personal connections they have established with the songs.